Increasing incidence of elderly onset patients with myasthenia gravis in a local area of Japan. Issue 10 (17th September 2009) - Matsui, N; Nakane, S; Nakagawa, Y; Kondo, K; Mitsui, T; Matsumoto, T; Arisawa, K; Kaji, R
Abstract : Objective: As the number of elderly patients with myasthenia gravis (MG) has recently increased in Europe and the USA, a retrospective survey of Japanese MG patients was conducted in a single neurological centre over several decades. Methods: The study consisted of 112 consecutive MG patients with onset of the disease from 1971 to 2006 from an area of approximately 0.8 million inhabitants in Japan. Patients were classified into three subgroups according to age at onset: young onset (39 years old), middle aged onset (40–59 years old) and elderly onset (60 years old). The trends in incidence rate and clinical features were examined: disease severity, seropositivity for antiacetylcholine receptor antibody, occurrence of other autoimmune diseases, occurrence of thymoma and therapeutic response. Results: The onset adjusted age specific average annual incidence per 100 000 of the elderly onset MG patients increased 20-fold from 1981–1990 (0.06; 95% CI 0.00 to 0.36) to 2001–2006 (1.30; 95% CI 0.77 to 2.05). Clinical features of the elderly onset MG patients included low antiacetylcholine receptor antibody titres (mean 24.6 nmol/l), less frequent autoimmune overlaps (8.0%) and nearly no complete stable remission with or without thymectomy. Conclusion: The increasing incidence of elderly onset MG in Japanese patients similar to that reported in Caucasians has been confirmed. The clinical features suggest different immunological backgrounds between young onset and elderly onset MG patients, irrespective of the ethnic background.